ENGINEERING AND GEOTECHNICAL SURVEYS AT THE SITE OF THE MAIN STRUCTURES OF THE PSKEM HYDROELECTRIC POWER STATION ON THE PSKEM RIVER - Назаров Комил Игамбердиевич; Хидоятов Захиджан Даливаевич; Хидоятов Абдуллох Захиджон ўғли (Journals Park Publishing, 2023)
This paper presents the results of geomechanical studies of the siltstone massif carried out in the right-bank experimental adit at the site of the Pskemskaya HPP dam. Primary shear experiments were carried out at the following 6 normal pressures on the stamp σ: 0.5 MPa; 1.0 MPa; 1.5 MPa; 2.0 MPa, 2.5 MPa and 3.0 MPa.
Keywords: stamp, strength, ultimate strength, siltstone, shear, shear angle, cracks.